Patrimonial Bureaucracy in Indonesia: Historical Roots, Institutional Manifestations, and Post-Reform Challenges - Irvan Ansyari; Tiara Elgi Fienda (Journal of Social and Policy Issues, 2026)
This study aims to examine the symptoms of Patrimonial Bureaucracy in the Indonesian government system, where this is the culture of Asian countries in general, especially regarding rewards, emotional closeness brought to the realm of bureaucracy and government. This article also aims to analyze the characteristics of patrimonial bureaucracy in Indonesia, the factors that drive it, and why various bureaucratic reform agendas have not fully succeeded in changing our bureaucratic system towards Weber's rational-legal model. This study uses a qualitative approach to library studies of various relevant academic literature, policy documents, reports of anti-corruption institutions, and investigative findings. This study found that patrimonial practices are manifested in the recruitment and promotion system based on connections (KKN), mass job mutations as a politics of rewards, and the use of public funds to strengthen patron-client networks. The main driving factors include the legacy of colonial and New Order bureaucracy, the weakness of the merit system, and the intervention of political party oligarchies into the bureaucratic machine. The impacts include inefficiency, budget leaks, poor public services, and the demoralization of professional civil servants. Patrimonial bureaucracy, characterized by personal relationships, patronage, and the mixing of public and private domains, remains a serious challenge in the post-reform Indonesian government system. Despite the Grand Design for Bureaucratic Reform 2010-2025 and the strengthening of the merit system through the Civil Servant Law, patrimonial resistance remains. This article concludes that bureaucratic reform in Indonesia requires political intervention and strengthening of public accountability.